Optically Tunable Field Effect Transistors with Conjugated Polymer Entailing Azobenzene Groups in the Side Chains. (1st February 2019) - Tian, Jianwu; Fu, Lulu; Liu, Zitong; Geng, Hua; Sun, Yanan; Lin, Gaobo; Zhang, Xisha; Zhang, Guanxin; Zhang, Deqing
Abstract: Semiconducting conjugated polymers with photoswitching behavior are highly demanded for field‐effect transistors (FETs) with tunable electronic properties. Herein a new design strategy is established for photoresponsive conjugated polymers by incorporating photochromic units (azobenzene) into the flexible side alkyl chains. It is shown that azobenzene groups in the side chains of the DPP (diketopyrrolopyrrole)‐quaterthiophene polymer (PDAZO ) can undergo trans / cis photoisomerization in fully reversible and fast manner. Optically tunable FETs with bistable states are successfully fabricated with thin films of PDAZO . The drain‐source currents are reduced by 80.1% after UV light irradiation for ≈28 s, which are easily restored after further visible light irradiation for ≈33 s. Such fast optically tunable FETs are not reported before. Moreover, such current photomodulation can be implemented for multiple light irradiation cycles with good photofatigue resistance. Additionally, thin film charge mobility of PDAZO can be reversibly modulated by alternating UV and visible light irradiations. On the basis of theoretical calculations and GIWAXS data, it is hypothesized that the dipole moment and configuration changes associated with the trans‐ / cis‐ photoisomerization of azobenzene groups in PDAZO can affect the respective intra‐chain and inter‐chain charge transporting, which is responsible for the optically tunable behavior for FETs with thin films of PDAZO . Abstract : Incorporation of azobenzene groups in the flexible side alkyl chains of the conjugated polymer leads to photoresponsive polymeric semiconductor and optically tunable field‐effect transistor with excellent switching performance.